(untitled) (Journal of International Studies, 2020)
There is hardly any dispute that the Eastern Indian Ocean like its historical past is once again emerging into a ‘cosmopolitan’ maritime arena underpinned by long stretches of peaceful exchange of commodities, energy and other maritime accessories. It has witnessed a new constellation of ‘inward-looking’ regional powers with a ‘bazaar nexus’ (for mercantile goods and energy supply) with Asian and non-Asian powers. Economically, small and middle powers of this region do share and accommodate all to draw the benefits of a highly globalised ‘closely-knit’ mercantile system. Problems relating to trade hazards—‘maritime mugging,’ ‘sea piracy,’ ‘illegal transfer of arms and ammunition, maritime terrorism, has already been addressed adequately by the collective effort of member nations under the aegis of ASEAN. This goodwill effort in the maritime zone awaits response from the cultural domain as well, which still lacks its frequency and luster of the glorious past. Although loads have been talked about, there has been little in action. The present paper is an attempt to study the community building efforts of ASEAN in connivance with emerging powers like India and China; and efforts at building up an Indian Ocean community as it existed in its past—sans feuds, sans fight—but unhindered exchange of culture and trade